Verification of mechanism for effect of silane coupling agent modification of polyethylene (PE) fiber's surface on strain-hardening behavior of high-strength cementitious composites. (15th May 2023) - Peng, Gai-Fei; Zhang, Gui; Lei, Ze-Hao; Ding, Hong; Jiang, Yu-Heng; Niu, Xu-Jing; Fan, Yu-Chun
Abstract: To fully understand the mechanism for the effect of silane coupling agent (SCA) modified polyethylene (PE) fiber on the strain-hardening behavior of high-strength cementitious composites (HSCC), an experimental research has been conducted, including direct tension and microstructural tests using optical microscope, scanning electron microscope (SEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The results showed that, compare to the interfacial bonding between original PE fiber and very high strength matrix of cementitious composite at water/binder ratio (W/B) of 0.18, the interfacial bonding was strengthened after the modification of PE fiber's surface by SCA solution of 3% concentration, which subsequently resulted in the improvement of initial-cracking stress, ultimate tensile stress and ultimate tensile strain from 5.20 MPa, 6.34 MPa and 0.68% to 7.26 MPa, 8.01 MPa and 5.06%, respectively. The mechanism for the improvement in strain-hardening behavior of HSCC with SCA-modified PE fiber was that the physicochemical interactions occurred between the SCA-modified PE fiber and the matrix. Among these interactions, amino and hydroxyl groups connected to the PE fiber improved the hydrophilicity of fiber surface, which enhanced the physical bonding between the SCA-modified PE fiber and the matrix. More importantly, two types of chemical interactions have been proved to establish chemical bonding between the PE fiber and matrix, namely, the condensation reaction between hydroxyl groups of the modification layer on the PE fiber and hydroxyl groups of C–S–H gels in the matrix, and the combination of the polymer of SCA's hydrolysates with Ca(OH)2 released by cement hydration. Highlights: Interfacial bonding between original PE fiber and high-strength matrix needs to be improved for better strain hardening. SCA modification can improve the strain-hardening behavior via physicochemical interactions between PE fiber and matrix. Failure mode of interfacial bonding between SCA-modified PE fiber and matrix is changed from ITZ failure to matrix failure.